2022
DOI: 10.3390/medicina58030366
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Participation, Sex Differences and Age of Peak Performance in Time-Limited Ultramarathon Events: A Secular Analysis

Abstract: Background and Objectives: Increases in the number of participants in time-limited ultra-marathons have been reported. However, no information is available regarding the trends in participation, performance and age in 12 h and 24 h time-limited events. The aim of the study was to describe the trends in runners’ participation, performance and age in 12 h and 24 h ultra-marathons for both sexes and to identify the age of peak performance, taking into account the ranking position and age categories. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Training routines and exercise habits of endurance runners active in running events were described by the following items regarding race distance: original and present motives to run (health, recreation, performance); favorite season and time of day to run (outdoors, indoors); total training timespan (duration preparing for the main race); training guidance (unsupervised, professional, or alternative); parallel sports participation (winter sports, summer sports); periodized training routines, including volume (weekly running sessions, average weekly and daily breadth of training (km, hours)) linked with training period and preparation conditions ( Hulteen et al, 2017 ; Waśkiewicz et al, 2019b ; Thuany et al, 2022a ; Yang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training routines and exercise habits of endurance runners active in running events were described by the following items regarding race distance: original and present motives to run (health, recreation, performance); favorite season and time of day to run (outdoors, indoors); total training timespan (duration preparing for the main race); training guidance (unsupervised, professional, or alternative); parallel sports participation (winter sports, summer sports); periodized training routines, including volume (weekly running sessions, average weekly and daily breadth of training (km, hours)) linked with training period and preparation conditions ( Hulteen et al, 2017 ; Waśkiewicz et al, 2019b ; Thuany et al, 2022a ; Yang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The global trends in sports and physical activities emphasize running as one of the main activities worldwide ( Hulteen et al, 2017 ). In long-distance running, the number of marathoners ( Thuany et al, 2022a ; Yang et al, 2022 ) and ultra-marathoners ( Thuany et al, 2022a ) has considerably increased in recent decades, with the motivations for training changing according to the distance ( Waśkiewicz et al, 2019a , b ). In marathon running, women focus more on body weight, life meaning, and self-esteem compared to men ( Waśkiewicz et al, 2019b ), whereas ultra-marathoners reported higher scores in affiliation and life meaning, and lower scores for weight concern, personal goal achievement, and self-esteem ( Waśkiewicz et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…Further emphasis for warranting research in this age-related area is the increasing popularity of ultra-endurance events among masters athletes (i. e. ≥ 40y), with a substantial increase in participation numbers among this age group [29,30]. This observation is of prime importance considering EIGS and Ex-GIS manifestations are predominantly and exaggeratively observed in such ultra-endurance events, and in some cases may impact performance outcomes and/or warrant medical attention [3,4,8,10,31].…”
Section: Does Age Influence Gastrointestinal Status Responses To Exer...mentioning
confidence: 99%
“…The percentage of female ultra-marathon competitors increased from close to 0 in the 1970s to about 10-20% in 2000 and remained fairly stable subsequently [73,74]. Since then, physiological differences between the sexes in EEE-relevant aspects are being increasingly acknowledged [75][76][77][78]. Female advantages may include greater fatigue resistance and substrate efficiency, as well as lower energetic demands [79].…”
Section: Sexmentioning
confidence: 99%